Mental health in times of pandemic: A literature review - Rozo-Sánchez, Astrid; Rivera-Porras, Diego; Pérez-Reyes, Ginna; García-Echeverri, Mabel; Cabrera-Gómez, Claudia Carolina; López-Jaimes, Ruth Jimena (Gaceta Médica de Caracas, 2021)
Society is going through a pandemic because of COVID-19 originating in Wuhan (China), which has triggered crises in all the nations of the world, which has transformed daily life, due to the measures taken by governments to stop the increase in infections. However, isolation, quarantine, concern, and fear of contagion and/or death have directly affected mental health. La sociedad está atravesando por una pandemia como consecuencia del COVID- 19 origina en Wuhan (China) que ha desencadenado crisis en todas las naciones delmundo, que ha transformado la cotidianidad, debido a las medidas tomadas por los gobiernos para detener el aumento de contagios, sin embargo, el aislamiento, la cuarentena, la preocupación y temor por el contagio y/o muerte ha afectado directamente la salud mental.